(Why) Does Evolution Favour Embryogenesis?. (July 2016) - Rensing, Stefan A.
Abstract : Complex multicellular organisms typically possess life cycles in which zygotes (formed by gamete fusion) and meiosis occur. Canonical animal embryogenesis describes development from zygote to birth. It involves polarisation of the egg/zygote, asymmetric cell divisions, establishment of axes, symmetry breaking, formation of organs, and parental nutrition (at least in early stages). Similar developmental patterns have independently evolved in other eukaryotic lineages, including land plants and brown algae. The question arises whether embryo-like structures and associated developmental processes recurrently emerge because they are local optima of the evolutionary landscape. To understand which evolutionary principles govern complex multicellularity, we need to analyse why and how similar processes evolve convergently – von Baer's and Haeckel's phylotypic stage revisited in other phyla. Trends: Complex multicellularity evolved several times independently in eukaryotes. After 150 years we have some molecular evidence for the hourglass pattern described by Haeckel. Developmental processes akin to animal embryogenesis are also known in land plants and some other lineages. Although it involves homologous genes, embryogenesis might not be homologous and it is unclear how and why it evolves.